CORRELATION BETWEEN ENDOTELIAL FUNCTION AND CHANGES OF VEIN BLOOD STREAM AT PATIENTS WITH ІІ STAGE HYPERTENTION - Tokarenko, O. I.; Andreeva, Y. O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
As a result of complex clinical and instrumental inspection 117 patients from the ІІ stage hypertension the character of changes of endotelial function and peripheral vein blood stream was set. It is set, that changes of vein link of circulation of blood has correlation chain with the indexes of endotelial function and can be observed even at patients without the presence of heart failure. The account of being of vein blood stream and endotelial function is recommended for the choice of therapy.